2016
DOI: 10.1002/ecs2.1267
|View full text |Cite
|
Sign up to set email alerts
|

Effects of climate change on phenologies and distributions of bumble bees and the plants they visit

Abstract: Surveys of bumble bees and the plants they visit, carried out in 1974 near the Rocky Mountain Biological Laboratory in Colorado, were repeated in 2007, thus permitting the testing of hypotheses arising from observed climate change over the intervening 33‐yr period. As expected, given an increase in average air temperature with climate warming and a declining temperature with increasing elevation, there have been significant shifts toward higher elevation for queens or workers or both, for most bumble bee speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
109
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(122 citation statements)
references
References 51 publications
7
109
1
1
Order By: Relevance
“…Although, some studies have shown temporal mismatch between some flowering plants and pollinators due to climate change (Burkle et al 2013;Robbirt et al 2014), there is a knowledge gap regarding such phenological mismatches between pollinator-dependent agricultural crops and bees, and their impact on pollination (Settele et al 2016). The potential for such phonological mismatch is greater for native bees such as bumble bees that hibernate during winter and whose emergence in spring is dependent on prevailing temperatures during the hibernation period (Pyke et al 2016).…”
Section: Fruit Crop Vulnerabilities and Expected Changes In The Northmentioning
confidence: 99%
“…Although, some studies have shown temporal mismatch between some flowering plants and pollinators due to climate change (Burkle et al 2013;Robbirt et al 2014), there is a knowledge gap regarding such phenological mismatches between pollinator-dependent agricultural crops and bees, and their impact on pollination (Settele et al 2016). The potential for such phonological mismatch is greater for native bees such as bumble bees that hibernate during winter and whose emergence in spring is dependent on prevailing temperatures during the hibernation period (Pyke et al 2016).…”
Section: Fruit Crop Vulnerabilities and Expected Changes In The Northmentioning
confidence: 99%
“…; Pyke et al . ), which in turn will severely affect the fitness of this species. It is very likely that some genetic variation is present in the populations, which is buffering against further loss of variation, and this might help preserve the potential for future adaptive changes.…”
Section: Discussionmentioning
confidence: 99%
“…Moeller and Geber 2005), increasing flowering synchrony among snowbed species may lead to a release of pollen limitation, which is regarded as being particularly strong in alpine plants (García-Camacho and Totland 2009). However, given the complex interplays between species flowering and interannual variation of environmental factors (Forrest et al 2010), and the possibility of warming-induced decrease in seasonal synchrony between plants and pollinators (Pyke et al 2016), it is not yet possible to predict these indirect effects of climatic changes on plants forming alpine snowbed communities.…”
Section: Warming Effects: Species Responses Over Time and Flowering Smentioning
confidence: 99%